An Ordinance Regulating the Carrying of Loaded Firearms in the City of Albany, Part 4, Ch. 72, § 1 in The Municipal Code of the City of Albany (1905). - (:unkn) unknown (General Publisher, 1905)
Any person, other than a peace officer, who shall in any public street, highway, or place within the city of Albany, have or carry concealed upon his person any loaded pistol, revolver, or other firearm, without theretofore having been authorized as hereinafter provided to carry the same, shall be guilty of a misdemeanor, punishable by a fine not exceeding one hundred and fifty dollars, or by imprisonment in a penitentiary or county jail for not more than one hundred and fifty days, or by both.
--
Keywords: CARRY - CONCEALED